Penguatan Pemberantasan Kejahatan Jalanan dan Aksi Premanisme Tahun 2023: Penguatan Pemberantasan Kejahatan Jalanan dan Aksi Premanisme Tahun 2023 - Saputra, Azis (Pusat Penelitian dan Pengembangan Polri, 2024)
Increasing development of society gives rise to various social changes which can take the form of changes to norms, regulations and habits. The impacts of social change is emergence of street crime and thuggery which can become a potential threat. Actions of thuggery can be carried out by small groups, as well as large groups. One of the National Police's programs is the eradication of thugs and acts of thuggery which is a follow-up to the National Action Plan. Therefore, Puslitbang Polri needs to conduct research on